Evaluating the Contents and Activities of a 6th Grade English Textbook in Bilingual School Context - najwa - najwa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Textbooks play a crucial role in shaping language learning experiences, particularly in bilingual school contexts where learners engage with more than one language simultaneously. This study aims to evaluate the content structure and learning activities of a sixth-grade English textbook used in a bilingual school, with a specific focus on skill integration and communicative development. Employing a qualitative descriptive design, the study uses Critical Discourse Analysis to examine Unit 3 “Chocolate” of the Our World 6 textbook. The analysis focuses on learning objectives, activity sequencing, skill integration, grammar presentation, and the communicative demands placed on learners. The findings reveal that the textbook demonstrates a clear and systematic content structure, beginning with learning objectives and schema-activating questions, followed by contextualized input and progressively communicative tasks. The learning activities integrate listening, speaking, reading, and writing skills through songs, texts, pair and group work, grammar practice, and project-based tasks. Although some activities remain form-focused, they function as scaffolding for younger learners and are balanced by meaningful interaction and real-life contexts. Overall, the study concludes that the textbook effectively supports communicative competence and integrated skill development, making it appropriate for sixth-grade learners in a bilingual school setting. The findings contribute to textbook evaluation research and offer insights for teachers, curriculum designers, and policymakers in selecting and developing English textbooks for bilingual education.